Constructing the Kwanja of Adamawa (Cameroon) : essay in fractal anthropology. - Gausset, Quentin (Lit, 2010)
The Kwanja are a small ethnic group of 10,000 people living in Adamawa, Cameroon. The present monograph describes their bilineal kinship system, political structures, oral history, moral economy, rituals, cosmologies and world view. The book discusses the way the Kwanja construct themselves as homogenous despite their astonishing cultural diversity (one can distinguish at least nine different groups speaking different languages and having a great variety of rituals), and how they construct themselves as different from their neighbours despite the cultural traits that they share in common. As the Fulbe dominate Adamawa economically and politically, the impact that they have on the construction of Kwanja society and identity is given prominent attention -- Présentation de l'éditeur.